Absent 'superimposed‐line' sign: novel marker in early diagnosis of cleft of fetal secondary palate. (1st December 2020) - Lakshmy, S. R.; Rose, N.; Masilamani, P.; Umapathy, S.; Ziyaulla, T.
ABSTRACT: Objectives: To describe a novel sign, the 'superimposed‐line' sign, for early diagnosis of cleft of the fetal secondary palate on two‐dimensional imaging of the vomeromaxillary junction in the midsagittal view. Methods: This was a prospective evaluation of the superimposed‐line sign using two‐dimensional sonography (midsagittal view) in 9576 singleton fetuses referred for routine screening between 12 and 20 weeks of gestation. In this view, the vomer bone appears as a line superimposed on the distal two‐thirds of the maxillary line, as the vomer fuses with the secondary palate in the midline. If there is a midline cleft of the secondary palate, the line formed by the palate is absent and hence only the vomer bone is visualized, creating a single line instead of the normal superimposed double line. Multiplanar three‐dimensional (3D) views were assessed in cases in which the superimposed‐line sign was absent. Results: The superimposed line was absent in 17 fetuses with a cleft of the secondary palate that was confirmed by 3D evaluation. Of these, 13 had defects involving the premaxilla and four had an isolated cleft of the secondary palate. Postnatal confirmation was available in all cases. The sign was useful in ruling out cleft of the fetal secondary palate in 32 high‐risk cases with a family history of cleft palate. The superimposed‐line sign had a sensitivity of 89.5% in detecting cleft of the secondary palate. Conclusions: The superimposed‐line sign is a new sonographic marker for evaluation of cleft of the fetal secondary palate; documentation of this sign proves the presence of both the palate and vomer in the midline. This marker can be demonstrated clearly in the late first trimester, allowing early diagnosis of secondary palatine cleft. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked article: There is a comment on this article by Lachmann and Brückmann. Click here to view the Correspondence.